Chronic lactate supplementation does not improve blood buffering capacity and repeated high‐intensity exercise. (23rd November 2016) - Oliveira, L. F.; de Salles Painelli, V.; Nemezio, K.; Gonçalves, L. S.; Yamaguchi, G.; Saunders, B.; Gualano, B.; Artioli, G. G.
Abstract : Since there is conflicting data on the buffering and ergogenic properties of calcium lactate (CL), we investigated the effect of chronic CL supplementation on blood pH, bicarbonate, and high‐intensity intermittent exercise performance. Sodium bicarbonate (SB) was used as a positive control. Eighteen athletes participated in this double‐blind, placebo‐controlled, crossover, fully counterbalanced study. All participants underwent three different treatments: placebo (PL), CL, and SB. The dose was identical in all conditions: 500 mg/kg BM divided into four daily individual doses of 125 mg/kg BM, for five consecutive days, followed by a 2–7‐day washout period. On the fifth day of supplementation, individuals undertook four 30‐s Wingate bouts for upper body with 3‐min recovery between bouts. Total mechanical work (TMW) for the overall protocol and for the initial (1st+2nd) and final (3rd+4th) bouts was determined at each session. Blood pH, bicarbonate, and lactate levels were determined at rest, immediately and 5 min after exercise. CL supplementation did not affect performance ( P > 0.05 for the overall TMW as well for initial and final bouts), nor did it affect blood bicarbonate and pH prior to exercise. SB supplementation improved performance by 2.9% for overall TMW ( P = 0.02) and 5.9% in the 3rd+4th bouts ( P = 0001). Compared to the control session, SB also promoted higher increases in blood bicarbonate than CL and PL (+0.03 ± 0.04 vs +0.009 ± 0.02 and +0.01 ± 0.03, respectively). CL supplementation was not capable of enhancing high‐intensity intermittent performance or changing extracellular buffering capacity challenging the notion that this dietary supplement is an effective buffering agent.